2016
DOI: 10.1155/2016/1830875
|View full text |Cite
|
Sign up to set email alerts
|

Acute Achilles Paratendinopathy following Major Injury of the Crural Fascia in a Professional Soccer Player: A Possible Correlation?

Abstract: Background. The anatomy and mechanical properties of the Crural Fascia (CF), the ubiquitous connective tissue of the posterior region of the leg, have recently been investigated. The most important findings are that (i) the CF may suffer structural damage from indirect trauma, (ii) structural changes of the CF may affect the biomechanics of tissues connected to it, causing myofascial pain syndromes, and (iii) the CF is in anatomical continuity with the Achilles paratenon. Consistent with these points, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Schulze et al, 2014 hypothesized its role in medial tibial stress syndrome and found that manual treatment of the crural fascia led to a reduction of pain in this condition. Mattiussi et al, 2016 suggested a potential role of this same fascia in acute Achilles Paratendinopathy. Further investigation may confirm these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Schulze et al, 2014 hypothesized its role in medial tibial stress syndrome and found that manual treatment of the crural fascia led to a reduction of pain in this condition. Mattiussi et al, 2016 suggested a potential role of this same fascia in acute Achilles Paratendinopathy. Further investigation may confirm these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, repetitive microtraumas to the gluteus maximus muscle from overuse and misuse led to myofascial pain syndrome (Waldman, 2014). Likewise, a recent report showed that the onset of acute Achilles paratendinopathy could be related to histological and biomechanical changes in the crural fascia resulting from calf muscles injury (Mattiussi et al, 2016). Another recent study described a case series of nine athletes with pain in the Achilles region who had tears in the fascia cruris from the attachment to the paratenon and AT (Webborn et al, 2015).…”
Section: Structural and Functional Coupling Between Muscles And Fasciamentioning
confidence: 99%